2016
DOI: 10.1007/s00432-016-2184-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble programmed cell death ligand 1 as a prognostic factor on the first-line treatment of metastatic or recurrent gastric cancer

Abstract: High serum levels of sPD-L1 correlated with worse overall survival on the first-line chemotherapy in metastatic GC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 58 publications
2
79
3
1
Order By: Relevance
“…An increasing number of studies have reported that sPD-1 and sPD-L1 might play crucial roles in the prediction of treatment responses and prognosis in cancer patients [1921]. However, the regulation, source and prognostic value of sPD-1/sPD-L1, as well as their association with clinicopathological factors in HCC, remain matters of debate.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported that sPD-1 and sPD-L1 might play crucial roles in the prediction of treatment responses and prognosis in cancer patients [1921]. However, the regulation, source and prognostic value of sPD-1/sPD-L1, as well as their association with clinicopathological factors in HCC, remain matters of debate.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, future studies should examine if PD-L1 blockade in vivo , with or without IL-10(R) blockade, results in similar therapeutic efficacy in ovarian cancer as seen with the PD-1 blockade. Lastly, another potentially important finding is that IL-10 activated release of soluble PD-L1 (sPD-L1), a form of PD-L1 which induces apoptosis of T cells and has been repeatedly shown to be associated with poor outcome in patients with advanced cancers (4145). …”
Section: Discussionmentioning
confidence: 99%
“…In other cancer entities, different approaches to determine prognostic cut-off values have been used: median sPD-L1 serum level in the analyzed cancer patient cohort, sPD-L1 serum levels in a corresponding cohort of healthy individuals or receiver operating characteristic (ROC) curve models to define an ideal prognostic cut-off value. [14][15][16][17][18] In all aforementioned studies, the prognostic cut-off value was in the range of the 50th (i.e., median) and 75th percentile of the observed sPD-L1 levels in the whole analyzed patient cohort. When designing our study we therefore decided to use the median and the 75th percentile of sPD-1 and sPD-L1 levels observed in our study to define a cohort of patients with high versus low levels of the two molecules.…”
Section: Spd-1 and Spd-l1 Elisasmentioning
confidence: 99%